Free Energy of Mixing of the Binary Liquid Alloys of Sodium - Chakrabarti, S. K.; Akhter, J.; Sinha, R. (Himalayan Physics, 2012)
Sodium is a highly reactive alkali metal. Within a binary liquid alloy it generally forms complexes. Due to formation of such complexes the thermodynamic properties of the binary alloys of sodium often show anomaly-deviating maximally from that of the ideal alloys. In the present work we have confined our investigation into the free energy of mixing (GM) of two binary alloys of sodium in liquid phase-Na-Pb and Na-Hg-near the melting point. For this purpose we have used Flory’s model and started with the activity of sodium in the sodium-lead liquid alloy and that of mercury in the sodium amalgam at molten stage. By the method of successive approximations we have ascertained the value of interchange energy for each alloy in the light of the experimental values of activity and finally computed GM for different concentrations of the constituent species. Our computation explains the observed symmetry and anomaly in the free energy of mixing of the Na-Pb and Na-Hg liquid alloys respectively. The Himalayan Physics Vol. 3, No. 3 2012 Page : 24-26